The Effect of Digital Device Usage on Student Academic Performance: A Case Study - Maria Limniou (MDPI AG, 2021)
The aim of this investigation was to explore student behaviour when students brought their own digital devices into a lecture theatre. A total of 361 undergraduate psychology students from the University of Liverpool who used at least one digital device during lecture time fully completed an online questionnaire (159 first-, 124 second- and 78 third-year psychology students) during the 2018-2019 academic year. Although all the three years of undergraduate students brought laptops and/or smartphones into a lecture theatre, there was no significant difference in academic performance over the years of studies. The findings have linked student multitasking processes in a lecture theatre to Social Cognitive Theory principles (reciprocal interactions between behaviours, learning environment, and individuals). There was a significant difference between the three years regarding the use of applications and student characteristics after controlling for the different types of devices. Students who used only one application during lecture time were more likely to achieve higher academic performance as they were less distracted from their primary tasks of processing and retaining information. Overall, this investigation concluded the importance of reconsidering the teaching delivery process so as to avoid students' escapism using devices during lecture theatres due to their engagement level and lecture norm pressures.